'It all depends on why it's red': qualitative interviews exploring patient and professional views of a traffic light system for in vitro fertilisation add-ons - Sarah Lensen; Sarah Armstrong; Emily Vaughan; Lucy Caughey; Michelle Peate; Cynthia Farquhar; Allan Pacey; Adam Balen; Elaine Wainwright (Bioscientifica, 2023)
In vitro fertilisation (IVF) add-ons are techniques, medicines, or procedures used in addition to standard IVF with the aim of improving the chance of success. The United Kingdom's IVF regulator, the Human Fertilisation Embryology Authority (HFEA) developed a traffic light system to categorise add-ons as either green, amber, or red, based on results of randomised controlled trials. We undertook qualitative interviews to explore understanding and views of the HFEA traffic light system among IVF clinicians, embryologists, and IVF patients across Australia and the United Kingdom (n = 73). Overall, participants were supportive of the intention of the traffic light system; however, many limitations were raised. It was widely recognised that a simple traffic light system necessarily omits information which may be important to understanding the evidence. In particular, the red category was used in scenarios that patients viewed as having different implications for their decision-making, including 'no evidence' and 'evidesssnce of harm'. Patients were surprised at the absence of any green add-ons and questioned the value of a traffic light system in this context. Many participants considered the website a helpful starting point, but desired more detail, including the contributing studies, results specific to patient demographics (e.g. <35 years and >35 years), and inclusion of more options (e.g. acupuncture). Overall, participants believed the website to be reliable and trustworthy, particularly due to the Government affiliation, and despite some concerns regarding transparency and an overly cautious regulator. The limitations of the traffic light system could be considered in any future updates to the HFEA website and others developing similar decision support tools.